Enzymatic complex in diets for gold fish fingerlings (Carassius auratus) - Signor, Arcângelo Augusto (2013)
Aiming to evaluate the enzymatic complex supplementation in diets for goldfish fingerlings (Carassius auratus), 240 fish weighing initially 1,36 ± 0,02g, randomly distributed in 20 tanks with 150L, in four treatments and five replications, with twelve fish in each experimental unit were used. The fish were fed at 8:00 and 11:00 a.m. and 2:00 and 5:00 p.m. with diets containing different inclusion levels (0; 0,033; 0,066 e 0,099%) of enzymatic complex (amilase, protease, celulase, lipase, ?-glucanase and phytase), and formulated with 32,36% of digestible protein and 3.023kcal of digestible energy kg-1. There were no differences observed (P>0,05) in the mean final weight, weight gain, total length, standard length, survival and carcass composition. However, the fish apparent feed conversion was impaired by the supplementation of enzymatic complex with 0,099% in diet. The use of enzymatic complex does not provides benefits in the productive performance for goldfish fingerlings.